PENINGKATAN AKTIVITAS DAN HASIL BELAJAR SISWA PADA MATA PELAJARAN MATEMATIKA DENGAN POKOK BAHASAN KESEBANGUNAN DAN SIMETRI BANGUN DATAR MELALUI METODE PROJECT BASED LEARNING DI KELAS V SDN 4 WRINGIN ANOM - Lusi Wahyu Apriyani; Indah Lestari Setiorini (Jurnal IKA PGSD (Ikatan Alumni PGSD) UNARS, 2015)
Education as a future other people in the world aims to have progress and also give solution in life. Study will be constructive if any inovation and choice the best to change the old way. This continue of every step in new methods of learning. Project Based Learning is one of new methods that support constructivis in education. The first special in this is how to make a team work to finished work from teacher. This work actually in three aspect, for example cognitive, affective and psycomotor. Category research is Classroom Action Research, in first step is observation at Grade Fifth Elementary School of Wringin Anom 4th, on March, 5th 2014. The methods can give progress in every cycle. Implementing of project based learning is reach 80% in cycle 1 and 100% in cycle 2. Learning activities is reach 77,84% in cycle 1 and 94,50% in cycle 2. Learning outcomes is reach 83,49% in cycle 1 and 94,48% in cycle 2. Means the method of Project Based Learning can improve learning outcomes and learning activities of Mathmatics grade V Elementary School Wringin Anom 4th